(3TQM cdjGJ GdbGfhf aj GdWH dGHf SjfGs - (3bWH GdOjf eMehO Hf eSYhO Hf eUdM GdTjQGRis; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s ((3YHO Gddg GdbjUQi s)
(3ChdgG (B:s
(3Ef Chdi eG GaJJM Hg NWGH MeO Gddg GdefYe HMjGI GdfahS hUMI GdCLSGe GdefbP ef GdCOhG GdeYVdI hGdCSbGe s
(3BNQgG (B:s
(3h GdCYVGA GdbhjI JOaY aVhdGJgG Edi LGQGJgG GdVYjaI dOaY GdbdH Edi GdEHWjf hGdOeGZ Edi GdNda GdCPfjf acdeG ELJeY ajg TF EfOaY Edi NGQL Je GdeLdO GdChd s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs